(untitled) (Dhaka University Journal of Science, 2016)
The complexes of Cu(II), Zn(II), Cd(II) and Hg(II) with adenine (AdeH) and uracil (UraH) have been synthesized and characterized by a combination of metal contents estimation, IR, UV-vis spectral data, thermogravimetric analysis (QSTG, TG and DSC) and magnetic susceptibility measurement. All the complexes are micro-crystalline, slightly soluble in water and decompose at high temperature. Both adenine and uracil deprotonated under experimental condition and then ligated to the metal ions as bidentate ligands through N(3) and N(9) of adeninato (Ade), and through N(3) and C(2)=O of uracilato (Ura) anions. On the basis of the metal contents, the complexes are formulated as [M(C5H4N5O)(C5H4N5)(H2O)2] [M = Cu(II), Zn(II) and Hg(II)] and [Cd(C5H4N5)(C4H3N2O2)(H2O)2].2H2O. The redox properties of copper and cadmium complexes were examined in aqueous solution by cyclic voltammetry. The voltammograms show quasi-reversible behavior for both the complexes. The X-ray powder diffraction study of the copper complex indicates that it is poorly crystalline in nature. Dhaka Univ. J. Sci. 64(2): 127-133, 2016 (July)